PEMENUHAN HAK AKSESIBILITAS FASILITAS PENYANDANG DISABILITAS PADA BIDANG PENDIDIKAN DI KABUPATEN SUKOHARJO - Hayati, Nayla Husnul; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This article examines how to fulfill the accessibility rights of facilities for persons with disabilities in the school environment in Sukoharjo Regency, namely at SMP Al Firdaus, SMPLB Langenharjo, SMP Negeri 1 Sukoharjo, SMP Negeri 2 Sukoharjo and SMP Negeri 4 Sukoharjo and the obstacles faced by providing education for persons with disabilities. especially the provision of facilities in school buildings. This article uses socio-legal or non doctrinal research methods with a qualitative approach. Legal sources are primary data (interviews and observations) and secondary data. The data analysis technique used is qualitative analysis. Based on the writing of this article, the conclusion is that the fulfillment of the accessibility rights of persons with disabilities at Al Firdaus Middle School, Langenharjo Middle School, State Junior High School 1 Sukoharjo, SMP Negeri 2 Sukoharjo and SMP Negeri 4 Sukoharjo are not yet in accordance with the facilities listed in the Minister of Public Works Regulation Number 302006 Regarding Technical Guidelines for Facilities and Accessibility in Buildings and the Environment and the obstacles to this implementation are that the existing regulations are not able to accommodate the needs of students with disabilities, inadequate human resources who are able to provide such accessibility, and the community paradigm for persons with disabilities in getting education.